The use of anti-crisis innovation with the financial restructuring of the organization . (Journal of Economic Research & Business Administration, 2015)
The article deals with the problems of the financial recovery of companies caught in crisis situations . Particular attention is paid to anti-crisis innovations for the production of products and the reorganization of production.
Keywords: crisis management innovation